Minojska formuła libacyjna w świetle stu lat badań - Zadka, Małgorzata (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The article is devoted to the examination of research into the so-called Minoan libation formula as known from the writings of Linear A.
Keywords: Crete; Minoan; linear A; libation formula